Differentiation of Medicinal Plants According to Solvents, Processing, Origin, and Season by Means of Multivariate Analysis of Spectroscopic and Liquid Chromatography Data - Burdejova, Lenka; Tobolkova, Blanka; Polovka, Martin; Neugebauerova, Jarmila (Molecules (Basel, Switzerland), 2023)
Effects of processing and extraction solvents on antioxidant properties and other characteristics were evaluated for ten medicinal plant species originating from two different localities and two production years. A combination of spectroscopic and liquid chromatography techniques possessed data for multivariate statistics. Water, 50% (v/v) ethanol, and dimethyl sulfoxide (DMSO) were compared to select the most suitable solvent for the isolation of functional components from the frozen/dried medicinal plants. DMSO and 50% (v/v) ethanol were evaluated as more efficient for phenolic compounds and colorants extraction, while water was more useful for element extraction. Drying and extraction of herbs with 50% (v/v) ethanol was the most appropriate treatment to ensure a high yield of most compounds. The satisfactory differentiation of herbs (61.8-100%) confirmed the significant effect of the processing, geographical, and seasonal factors on target functional component concentrations. Total phenolic and total flavonoid compounds content, total antioxidant activity expressed as TAA, yellowness, chroma, and browning index were identified as the most important markers for medicinal plant differentiation.
Keywords: Plant Extracts; Chromatography, Liquid; multivariate statistical analysis; multi-experimental analysis; medicinal plants; processing and seasonal factor; Multivariate Analysis; Plants, Medicinal; ethanol; Solvents; geographical origin; fenoly; Antioxidants; rostlinné extrakty; rozpouštědla; antioxidancia; roční období; chromatografie kapalinová; multivariační analýza; Seasons; voda; Phenols; dimethylsulfoxid; Water; Ethanol; léčivé rostliny; solvent effect; Dimethyl Sulfoxide